Controlled exchange bias behavior of manganese nanoparticles - Tiwari, Garima; Vinod, C. Prabhakaran; Jagirdar, Balaji R. (Journal of Magnetism and Magnetic Materials, 2022)
Mn(0) colloids were synthesized by solvated metal atom dispersion approach utilizing hexadecylamine, toluene, and THF as coordinating ligands. Mn-toluene and Mn-THF nanoparticles were found to be highly pyrophoric in nature and demand careful handling whereas, Mn-HDA nanoparticles undergo slow oxidation. TEM micrographs revealed formation of nanoparticles between 3 and 6 nm. Magnetic studies of these three samples displayed shift in the field-cooled M-H hysteresis loop which has been attributed to exchange bias behavior. The exchange bias field, HE measured at 5 K varies with change in coordinating ligands around the Mn center which are 1217 Oe, 4408 Oe and, 6350 Oe for Mn-HDA, Mn-toluene and Mn-THF nanoparticles, respectively. The large exchange bias field has been attributed to the presence of uncompensated antiferromagnetic surface spins and the exchange interactions at the nanoparticle surface due to surface oxidation.
Keywords: Antiferromagnetism; exchange bias; Ferromagnetism; Manganese nanoparticles; Uncompensated spins

Reactivity of four coordinate iridium complex towards hydrogen: an experimental and computational study - Agrawal, Nisha K.; Dash, Soumya R.; Vanka, Kumar; Nethaji, Munirathinam; Jagirdar, Balaji R. (Journal of Organometallic Chemistry, 2022)
Reaction of a four coordinate, 16-electron Ir complex, [Ir-(iPr)4(POCOP)(PPh3)] (4 ) (((iPr)4)(POCOP= 2,6-bis(di-isopropyl phosphinito)benzene, kappa(3)-C6H3-1,3-[OP((iPr))(2)](2)), with H-2 resulted in an oxidative addition product, cis-dihydride complex, cis-[Ir(H)(2) ((iPr)4)(POCOP)(PPh3)] ( cis-5 ) presumably via the intermediacy of a sigma complex, [Ir(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)]. The cis-dihydride complex completely isomerizes to the trans-dihydride complex trans-[Ir(H)(2) ((iPr)4)(POCOP)(PPh3)] ( trans-5 ) under ambient conditions in about 3 h. It was found that the steric and electronic features on the iridium center have significant influence on the approach of H-2 onto the metal center followed by oxidative addition and isomerization. The isomerization process was studied in detail and all the mechanistic aspects have been elucidated using a combination of both experimental work and computation. The cis-dihydride complex isomerizes to the trans-dihydride by compensating the trans influence of the strongly trans-directing hydride ligand. A mechanism involving the exchange of the position of PPh3 with a hydride ligand cis to itself via PPh3 dissociation and re-coordination thereby resulting in the formation of the trans-dihydride complex, has been proposed for the isomerization. The cis-dihydride was found to be a highly active catalyst for hydrogenation of ethy-lene. A competing reactivity study of cis-dihydride between isomerization versus insertion of C2H4 into the Ir-H bond, was studied experimentally and computationally. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Hydrogenation; Insertion; iridium complex; isomerization; Oxidative addition; Reductive elimination

Dual routes toward observation of a trans-H2/hydride complex in an iridium pincer system and hydrogenation catalytic activity - Agrawal, Nisha K.; Dash, Soumya R.; Vanka, Kumar; Jagirdar, Balaji R. (Organometallics, 2023)
The Abstraction of chloride from a six- coordinate complex, trans-[ Ir(H)(Cl)((iPr)4)(POCOP)(PPh3)] (1) [((iPr)4)(POCOP) = 2,6-bis(di-iso-propylphosphinito)benzene,kappa(3)-C6H3-1,3-[OP(Pr-i)(2 )](2)], using NaBAr4f leads to the generation of a dinitrogen complex, trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)][BAr4f] (6). Addition of H-2 to [Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)](+) (6) under extremely mild conditions (1 bar, 298 K) resulted in the reversible coordination of H-2 to generate the cis-[Ir(H)(eta H-2-(2))((iPr)4)(POCOP)(PPh3)](+) (cis-11) complex. The cis-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) complex (cis-11) isomerized to a trans isomer, trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) (trans-11), at 253 K. The isomerization process has been studied and supported by computations. Employing an alternative route, protonation of the trans-[Ir(H)(2)((iPr)4)(POCOP)(PPh3)] complex (2) at 183 K resulted in the formation of an identical, trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) complex (trans-11); upon warming the sample, the trans-H-2/hydride complex isomerized to the cis isomer above 253 K. Two independent routes to obtain trans-[Ir(H)(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)](+) (trans-11) species have been established. Reaction of trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)][BAr4f] (6) with C2H4 gave the cis-[Ir(H)(eta(2)-C2H4)((iPr)4)(POCOP)(PPh3)](+) complex (cis-15), which also undergoes isomerization to yield an equilibrium mixture of cis/trans-[Ir(H)(eta(2)-C2H4)((iPr)4)(POCOP)(PPh3)](+) complexes (cis-15 and trans-15) at 253 K. The trans-[Ir(H)(N-2)((iPr)4)(POCOP)(PPh3)](+) complex (6) is an excellent catalyst for hydrogenation of ethylene to ethane under very mild conditions.

H-atom site exchange in an iridium trans-dihydrogen/hydride complex, trans-[Ir(H)(?2-H2)(iPr)4(POCOP)(DMAP)]+ - Agrawal, Nisha K.; Gayathridevi, S.; Dash, Soumya R.; Vanka, Kumar; Jagirdar, Balaji R. (Dalton Transactions, 2023)
Treatment of trans-[Ir(H)(N)(2)((iPr)4)(POCOP)(DMAP)][BAr4f] (2) with H-2 (1 bar) under ambient conditions (298 K) results in the formation of a trans-[Ir(H)(?(2)-H-2)((iPr)4)(POCOP)(DMAP)][BAr4f] (3) complex. Complex 3 exhibits H-atom site exchange between the bound H-2 and the hydride ligands which are mutually trans to one another. A plausible mechanism of this exchange involves metal-ligand cooperativity as studied by computations.

Heterolytic cleavage of the B–H bond in H3B·L (L = THF, NMe2H) by an electrophilic Ir(iii) pincer complex [Ir(H)(PMe3)(tBu4POCOP)][BAr F4] - Pradhan, Mitarani; Surati, Zeel Y.; Pal, Apurba Kumar; Vanka, Kumar; Jagirdar, Balaji R. (2025)
<div class="abstract author" id="aep-abstract-id6" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> Six- and five-coordinate iridium complexes, [Ir(H)Cl(PMe3)(tBu4POCOP)] (2) (tBu4POCOP = κ3-C6H3-2,6-(OPtBu2)2) and [Ir(H)(PMe3)(tBu4POCOP)][BArF4] (3), respectively, have been synthesized and characterized. The reactivity of the electrophilic 16-electron iridium(III) complex 3 with H2, H3B·THF, H3B·NMe2H, and H3B·NMe3 was investigated. The reaction of complex 3 with H2 resulted in the formation of trans-[Ir(H)(η2-H2)(PMe3)(tBu4POCOP)][BArF4] complex 5. Complex 3 was found to activate the B–H bonds in H3B·THF and H3B·NMe2H (DMAB) in a heterolytic fashion. The reaction of complex 3 with H3B·THF at 298 K afforded trans-[Ir(H)2PMe3(tBu4POCOP)] complex 6 and a boronium compound, [H2B(THF)2][BArF4]. Monitoring the reaction from 179 to 298 K by NMR spectroscopy revealed the formation of a σ-borane intermediate, trans-[Ir(H)(η1-HBH2·THF)PMe3(tBu4POCOP)][BArF4] (3a-Int), en route to the final products observed at 298 K. The formation of this intermediate species was also investigated by density functional theory (DFT) calculations. The reaction of complex 3 with H3B·NMe2H at 298 K yielded a mixture of complexes 3 and 5 and a cyclic diborazane [H2BNMe2]2. The reaction was found to proceed via intermediates, a σ-borane complex, trans-[Ir(H)(η1-HBH2·NMe2H)PMe3(tBu4POCOP)][BArF4] (3b), complex 6, [(NHMe2)2BH2][BArF4], and H2B<img alt="[double bond, length as m-dash]" border="0" src="https://www.rsc.org/images/entities/char_e001.gif" style="border: none; color: rgba(0, 0, 0, 0.79); font-family: "Source Sans Pro", source-sans-pro, museo_sans300, museo-sans, Arial, sans-serif;" />NMe2. Complex 3 exhibited no reactivity with H3B·NMe3.